Archetypes and the Iconic Unconscious: Jung, Benjamin, Adorno and the “strong program” in Cultural Sociology - Mele, Vincenzo (Italian Sociological Review, 2026)
This article explores the heuristic potential of C. G. Jung’s concepts of archetype and collective unconscious within the sociology of the imaginary, connecting them to the debate between Walter Benjamin and Theodor W. Adorno on the Arcades Project. Through a comparison between Jung’s depth psychology, Benjamin’s critique of modernity, and Adorno’s theory of culture, the study shows how the archaic imaginary may serve as an interpretative key to the symbolic and mythical dynamics of capitalist modernity. The article also discusses the contemporary relevance of these concepts in relation to the “strong program” in cultural sociology and the iconic turn, arguing that Jeffrey Alexander’s notion of iconic consciousness can be reinterpreted through Benjamin’s idea of an iconic unconscious. The aim is to outline the foundations of a sociology of the imaginary able to integrate the symbolic, emotional, and material dimensions of social experience.